2006
DOI: 10.1038/nature04518
|View full text |Cite
|
Sign up to set email alerts
|

RNA-mediated response to heat shock in mammalian cells

Abstract: The heat-shock transcription factor 1 (HSF1) has an important role in the heat-shock response in vertebrates by inducing the expression of heat-shock proteins (HSPs) and other cytoprotective proteins. HSF1 is present in unstressed cells in an inactive monomeric form and becomes activated by heat and other stress stimuli. HSF1 activation involves trimerization and acquisition of a site-specific DNA-binding activity, which is negatively regulated by interaction with certain HSPs. Here we show that HSF1 activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
255
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(258 citation statements)
references
References 30 publications
3
255
0
Order By: Relevance
“…Evf-2 thus appears to be acting at least partially as a RNA-based transcriptional coactivator. This potential function is not unprecedented, as the ncRNA SRA has been known for some time to act as a transcriptional coactivator by directly interacting with steroid receptors (Lanz et al, 1999), while the ncRNAs NRSE and HSR have been shown to regulate the activity of REST and HSF-1, respectively (Kuwabara et al, 2004;Shamovsky et al, 2006). However, the story is likely more complex for Evf-2.…”
Section: How Might Osts Work?mentioning
confidence: 99%
“…Evf-2 thus appears to be acting at least partially as a RNA-based transcriptional coactivator. This potential function is not unprecedented, as the ncRNA SRA has been known for some time to act as a transcriptional coactivator by directly interacting with steroid receptors (Lanz et al, 1999), while the ncRNAs NRSE and HSR have been shown to regulate the activity of REST and HSF-1, respectively (Kuwabara et al, 2004;Shamovsky et al, 2006). However, the story is likely more complex for Evf-2.…”
Section: How Might Osts Work?mentioning
confidence: 99%
“…Upon stress, HSF1 becomes trimerized, binds to the heat-shock elements present in the HSP promoters, and rescues the RNA pol II elongation complex from promoter-proximal arrest (Shopland et al 1995;Shopland and Lis 1996). A recent study has shown that HSF1 activation by heat shock is an active process and is mediated by a ribonucleoprotein complex containing translation elongation factor eEF1A and a newly identified ncRNA, HSR-1 (Shamovsky et al 2006). HSR-1 RNA is an ∼600-nt poly(A) − RNA and shows a high degree of homology between human and rodents.…”
Section: Heat Shock Rna-1 (Hsr-1)mentioning
confidence: 99%
“…37,38 Upregulation of EF1α has been associated with cell death. 38,39 Our finding that HDM2 interacts with EF1α suggests that they may modulate each others function. A recent publication 39 described a role of EF1α in activation of a transcription factor heat shock factor 1 (HSF1).…”
Section: Resultsmentioning
confidence: 96%